Pengaruh Sense Of Community & Inter-Role Conflict Terhadap Academic Procrastination Mahasiswa (Survei terhadap Mahasiswa Organisatoris Angkatan 2022 di Fakultas Keguruan dan Ilmu Pendidikan Universitas Siliwangi) - Putri, Rivani Fardiana; Gumilar, Rendra; Kurniawan, Kurniawan (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
The problem in this study is the low Academic Procrastination in organizational students, the purpose of this study is to determine the effect of Sense of Community and Inter-Role Conflict on Academic Procrastination. This research uses quantitative methods. The population in this study were Organizational Students of Class 2022, Faculty of Teacher Training and Education, Siliwangi University, namely 220 people. In this study, the sampling technique used was nonprobability sampling using saturated sampling. The data collection method used a questionnaire and the data analysis technique used multiple linear regression analysis with the T Test and F Test. The results of data processing obtained that Academic Procrastination shows a moderate category of 12,076, Sense of Community shows a moderate category of 11,684 and Inter-Role Conflict shows a moderate category of 15,877. Partial Test Results show that Sense of Community has a significant positive effect on Academic Procrastination with a significance value of 0.000, Inter-Role Conflict has a significant positive effect on Academic Procrastination with a significance value of 0.000 and Simultaneous Test Results show that Sense of Community and Inter-Role Conflict have a significant effect on Academic Procrastination with a significance value of 0.000. The conclusion of this study is that there is a significant influence of Sense of Community and Inter-Role Conflict on Academic Procrastination with a significance value of 0.000. The conclusion of this study is that there is a significant influence of Sense of Community and Inter-Role Conflict on Academic Procrastination with a coefficient of determination of 77%.